Distalization of the mandibular first molar with clear aligners: a 3D finite element study - Kang, Fujia; Xu, Yifei; Zhao, Xinyan; Lu, Zhen; Li, Dongning; Zhao, Jiamin; Li, Yibao; Li, Menghong; Qi, Kun (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionThis study aims to analyze the impact of varying initial positions of the mandibular first molar and attachment configurations on tooth movement by finite element analysis (FEA).MethodsA three-dimensional (3D) model was constructed, including the mandible, dentition, periodontal ligaments (PDLs), clear aligners (CAs), and attachments. The second molar was initially positioned 3.2 mm distally. Groups were defined as follows: no attachment, attachment on the second molar (second molar ATT), and attachment on the first molar (first molar ATT). In each group, the first molar’s initial position relative to the second premolar varied (0 mm, 1 mm, 2 mm, and 3 mm). The displacement was extracted for result analysis.ResultsWith distal movement of the first molar’s initial position, distal displacement of the first molar, mesial displacement of the premolars, and labial displacement of the anterior teeth increased from 9.18e−2 to 1.12e−1 mm, from 1.32e−2 to 4.16e−2 mm, and from 4.07e−2 to 4.69e−2 mm, respectively, while mesial displacement of the second molar decreased from 4.59e−2 to 2.96e−2 mm in the NO ATT group. Displacement of the first molar, premolars, and anterior teeth in the first molar ATT group was greater than that in the other groups. For the second molar, the most significant mesial displacement was observed in the second molar ATT group.ConclusionWithout additional anchorage, the distal displacement of the first molar is concomitant with the opposite movement of other teeth in the dentition. With distal movement of the first molar’s initial position, the movement efficiency of the mandibular first molar increased. Therefore, increased step distance in precedence can be designed to enhance the overall movement efficiency.